2020
DOI: 10.7759/cureus.10711
|View full text |Cite
|
Sign up to set email alerts
|

Can Continuous Local Anesthetic Infusion After Median Sternotomy Reduce Opioid Use?

Abstract: Introduction Effective treatment of postoperative pain due to median sternotomy speeds up hemodynamic healing of patients. For this purpose, opioids with a wide range of side effects are widely used at high doses. The aim of this study is to investigate the effect of continuous local anesthetic (bupivacaine) infusion on opioid use on cardiac surgery patients undergoing median sternotomy. Methods A total of 215 patients undergoing isolated coronary artery bypass grafting surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Pharmacological techniques, such as opioids and anti-inflammatory drugs, infiltration with local anesthetics, nerve blocks, and spinal analgesia 12 , and non-pharmacological techniques, such as heat/cold application, massage, hypnosis, and distraction techniques, exist. Continuous infusion of local anesthetics can reduce the intensity of acute postoperative pain, opioid use, mechanical ventilation time, hospital stay, and atelectasis, and it is a simple and effective method for treating pain after median sternotomy 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological techniques, such as opioids and anti-inflammatory drugs, infiltration with local anesthetics, nerve blocks, and spinal analgesia 12 , and non-pharmacological techniques, such as heat/cold application, massage, hypnosis, and distraction techniques, exist. Continuous infusion of local anesthetics can reduce the intensity of acute postoperative pain, opioid use, mechanical ventilation time, hospital stay, and atelectasis, and it is a simple and effective method for treating pain after median sternotomy 23 .…”
Section: Discussionmentioning
confidence: 99%
“…When combined with high heterogeneity, this may bias the results of a random-effects meta-analysis by over-emphasizing the contributions of smaller studies with higher observed effect sizes. Abassi et al 13 NA NA Agarwal et al 14 4/44 0/41 29 NA NA…”
Section: Limitationsmentioning
confidence: 99%